«The Time of Ordeal»: A Literary Consideration of the 1916 Revolt - M., Auezova Z. (Farabi Journal of Social Sciences, 2019)
Abstract. For Central Asian history, this year marks the hundredth anniversary of the massive revolt in Turkestan and the Steppe Regions (Krai’s), which cost thousands of lives. It consisted of a series of local manifestations and armed attacks against the Russian administration and settlers, whose pressure had been becoming particularly harsh during World War I. In an attempt to escape the massacre, several Kazakh and Kyrgyz clans fled as far away as China. The revolt broke up as reaction to tsar’s edict of June 25, 1916 ordering males of non-Russian origin aged 19-43 to register for work at military installations of the Russian army. This was the second year of Russia’s participation in the «Great War», which led to huge losses in men and materiel.